The THE INFLUENCE OF LEARNING INTEREST ON STUDENTS LEARNING OUTCOMES IN SUBJECT - Novia Nurul Chasanah; Rahma Sukmaningrum; Erny Wahyuni (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The purpose of this study was to determine the Influence of Learning Interests on Student Learning Outcomes in Man 2 Semarang. Students of Man 2 Semarang were the object of this study. This study also serves to see how important student interest in learning to student learning outcomes in English subjects at the senior high school level. The sample was conducted on 33 students of Man 2 Semarang. The sampling technique used purposive sampling in which the respondents were some of the students of MAN 2 Semarang. The data collected by distributing questionnaires using a 4-point Likert scale to measure 8 statement items. The analysis technique used was linear regression analysis. The results showed that first, students' interest in learning simultaneously had a significant effect on student learning outcomes. Second, student learning interest had a partial and significant impact on student learning outcomes.